Tenecteplase in ischemic stroke offers improved recanalization: Analysis of 2 trials. (4th July 2017) - Bivard, Andrew; Huang, Xuya; Levi, Christopher R.; Spratt, Neil; Campbell, Bruce C.V.; Cheripelli, Bharath Kumar; Kalladka, Dheeraj; Moreton, Fiona Catherine; Ford, Ian; Bladin, Christopher F.; Davis, Stephen M.; Donnan, Geoffrey A.; et al.
Abstract : Objective: To test whether patients with complete vessel occlusion show greater recanalization at 24 hours and have improved clinical outcomes at 24 hours and 90 days when treated with tenecteplase compared to alteplase. Methods: Pooled clinical and imaging data from 2 phase 2 randomized trials comparing tenecteplase with alteplase allowed CT angiography (CTA) scans to be assessed centrally for occlusion status at baseline and at 24 hours post thrombolysis using the modified thrombolysis in cerebral infarction (TICI) scale. Twenty-four-hour poststroke NIH Stroke Scale (NIHSS) and 90-day modified Rankin Scale (mRS) scores were also compared between treatment groups using linear regression to generate odds ratios (ORs). Results: From 146 pooled patients, 69 had a TICI 0/1 occlusion overall at baseline. Tenecteplase-treated patients with a complete vessel occlusion had greater complete recanalization rates at 24 hours (71% for tenecteplase vs 43% for alteplase, p < 0.001). Patients with a TICI 0/1 occlusion who were treated with tenecteplase also showed greater early clinical improvement (median NIHSS change with tenecteplase was 9, interquartile range [IQR] 6, alteplase 1, IQR 1, p = 0.001) and higher rates of favorable 90-day outcomes (mRS 0–1 of tenecteplase compared with alteplase, OR 4.82, 95% confidence interval 1.02–7.84, p = 0.05). Conclusions: Tenecteplase may offer greater recanalization efficacy compared to alteplase, possibly exaggerated in patients with complete vessel occlusions on baseline CTA.